Can Transnational Cooperation Support Municipalities to Address Challenges of Youth Migration? - Gruber, Elisabeth (2021)
In the cooperation project ‘YOUMIG,’ funded by the INTERREG Danube transnational programme, challenges of youth migration were discussed in a transnational consortium consisting of project partners from different countries from Central and Eastern Europe experiencing difficulties such as a declining population and outmigration, as well as immigration of young people, which necessitated the provision of an integration infrastructure. Project outcomes included strategies as well as pilot activities performed by local-level authorities. The following article will consider outcomes as well as experiences from stakeholders involved in the project and investigate individual and organizational learning processes throughout the project. It will elaborate on the question of the extent to which transnational cooperation can potentially facilitate sustainable institutional changes and transformation. The results confirm the potential of transnational cooperation towards triggering learning and institutional change. Nevertheless, they underline that in the context of the project, the learning processes that could be achieved were predominantly of an individual nature and that the tangible outcomes could not lead to sustainable institutional changes.